2007
DOI: 10.1158/1078-0432.ccr-07-1152
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Carcinogenic Progression to Esophageal Adenocarcinoma by the Manganese Superoxide Dismutase Supplementation

Abstract: Purpose: Oxidative stress is related to the carcinogenic pathway of reflux esophagitis to Barrett's metaplasia to esophageal adenocarcinoma (EAC). Recent studies have shown that a decreased manganese superoxide dismutase (MnSOD) level is associated with the increased incidences of Barrett's esophagus (BE) and EAC. The aim of this study was to investigate MnSOD supplementation as a chemopreventive agent to prevent oxidative injury and subsequent BE and EAC formation. Experimental Design: Our esophagoduodenal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
(24 reference statements)
1
32
0
Order By: Relevance
“…As expected, MnTBAP 3À lacks efficacy in the O 2 ·À -specific model of aerobic growth of SOD-deficient E. coli (31,262). MnTBAP 3À (most likely in some impure form) has been used in numerous studies (73,76,194,206,229,251). Most of the reports assigned the effects observed in vivo to MnTBAP 3À SOD-like activity.…”
Section: Electrostaticsmentioning
confidence: 71%
See 1 more Smart Citation
“…As expected, MnTBAP 3À lacks efficacy in the O 2 ·À -specific model of aerobic growth of SOD-deficient E. coli (31,262). MnTBAP 3À (most likely in some impure form) has been used in numerous studies (73,76,194,206,229,251). Most of the reports assigned the effects observed in vivo to MnTBAP 3À SOD-like activity.…”
Section: Electrostaticsmentioning
confidence: 71%
“…Although the effects observed may be real, mechanistic explanations attributing them to an SOD-like activity of MnTBAP 3À are likely not real (73,76,194,206,229,251). As already mentioned, either the effects are due to the SOD-like impurities or the MnTBAP 3À acts through ONOO À -mediated pathways.…”
Section: Reactivity Towardmentioning
confidence: 91%
“…In human esophageal cancers, studies have shown that decreased MnSOD levels are associated with increased incidences of esophageal adenocarcinoma (EAC) (82).…”
Section: Sods and Early Stage Cancer Preventionmentioning
confidence: 99%
“…It has been demonstrated that metalloporphyrins with higher SOD activity have higher CAT activity suggesting the utility of SOD mimetics in ROS-mediated in vitro and in vivo models of disease (104). In an EAC rat model, the SOD mimetic Mn(III)tetrakis(4-benzoic acid) porphyrin (MnTBAP) decreased the incidence of EAC, which is correlated with a 25% increase in SOD enzymatic activities, suggesting MnTBAP may be able to serve as a chemopreventive agent for EAC (82). Another SOD mimetic (MnTE-2-PyP 5 + ) has been tested in the chemically-induced skin carcinogenesis mouse model (158).…”
Section: Sods and Early Stage Cancer Preventionmentioning
confidence: 99%
“…The metalloporphyrin manganese superoxide dismutase (MnSOD) mimetic, MnTBAP, is such an alternative antioxidant [174], that induces cancer cell death by increasing H 2 0 2 [173], yet inhibits cardiotoxicity induced by the anthraquinone derivative chemotherapeutic, Doxorubicin [175], and acute liver failure [176]. In addition, the antioxidant properties of MnTBAP may be chemopreventive against esophageal adenocarcinoma [177]. Alternatively, the recent development of the Hsp90-hinding non-quinone analog of GA, analog 5 of macbecin, may provide cancer therapies that are less toxic to normal cells [178].…”
Section: The Mechanisms Of Ga Cytotoxicitymentioning
confidence: 99%